Association between various blood glucose variability-related indicators during early ICU admission and 28-day mortality in non-diabetic patients with sepsis - Jingyan Zhou; Zhiheng Chen; Hao-Neng Huang; Chun-Quan Ou; Xin Li (Diabetology & Metabolic Syndrome)
Abstract Background Various blood glucose (BG) variability-related indexes have been widely used to assess glycemic control and predict glycemic risks, but the association between BG variations and prognosis in non-diabetic patients with sepsis remains unclear. Methods The single-center retrospective cohort study included 7,049 non-diabetic adults with sepsis who had at least 3 records of bedside capillary point of care BG testing during the first day after ICU admission from MIMIC-IV database (2008 to 2019). Coefficient of variation and standard deviation of glucose (i.e., GluCV and GluSD), M-value, J-index, high blood glucose index (HBGI), and low blood glucose index (LBGI) were used to describe glucose variability, quality of glycemic control, and glycemic risk of patients with sepsis. The dose-response relationship between BG variability-related indexes and mortality was explored using multivariate logistic regression with restricted cubic spline (RCS) function. If the dose-response curve presented a J-shape with a specific threshold value, a linear threshold function instead of RCS would be employed. Results There is a J-shaped relationship between hospital mortality risk and glucose variability-related indexes in ICU patients with sepsis. The mortality risk remained relatively stable below the threshold of these indexes. However, over the threshold, the 28-day mortality risk increased by 2.82% (95% CI: 1.80–3.85%), 1.13% (95% CI: 0.66–1.60%), 1.96% (95% CI: 0.98–2.95%), 1.37% (95% CI: 0.57–2.16%), 11.19% (95% CI: 6.56–15.98%) and 39.04% (95% CI: 29.86–48.81%) for each unit increases in GluCV, GluSD, M-value, J-index, LBGI and HBGI, respectively. The effects of LBGI and HBGI on 7-day and 14-day mortality were more pronounced. Conclusions High levels of GluCV, GluSD, M-value, J-index, HBGI, and LBGI on the first day of ICU admission were important risk markers of hospital mortality among non-diabetic patients with sepsis.